2014
DOI: 10.1051/0004-6361/201424049
|View full text |Cite
|
Sign up to set email alerts
|

Wave dynamics in a sunspot umbra

Abstract: Context. Sunspot oscillations are one of the most frequently studied wave phenomena in the solar atmosphere. Understanding the basic physical processes responsible for sunspot oscillations requires detailed information about their fine structure. Aims. We aim to reveal the relationship between the fine horizontal and vertical structure, time evolution, and the fine spectral structure of oscillations in a sunspot umbra. Methods. The high spatial and time resolution data obtained with SDO/AIA for the sunspot in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 31 publications
7
52
0
Order By: Relevance
“…travelling through umbra to penumbra (Zirin & Stein 1972;Giovanelli 1972;Sych & Nakariakov 2014;Su et al 2016). Figure 5 shows two scenarios for both local and nonlocal in sunspots.…”
Section: Scenarios Of Local and Nonlocal Sunspot Oscillationsmentioning
confidence: 99%
“…travelling through umbra to penumbra (Zirin & Stein 1972;Giovanelli 1972;Sych & Nakariakov 2014;Su et al 2016). Figure 5 shows two scenarios for both local and nonlocal in sunspots.…”
Section: Scenarios Of Local and Nonlocal Sunspot Oscillationsmentioning
confidence: 99%
“…A recent study of the relation of the umbral fine structure and waves from AIA/SDO images by Sych and Nakariakov (2014) revealed the enhancements of the oscillation amplitude that have a peculiar structure consisting of an evolving two-armed spiral and a stationary circular patch at the spiral origin, situated near the umbra center. This structure is observed at all layers observed by AIA, from the temperature minimum to the corona.…”
Section: Fine Structure Of Umbral Wavesmentioning
confidence: 99%
“…Interestingly, recent observational works reported that in the horizontal plane, 3 minute oscillations often appear in sunspot umbrae as one-and two-armed spiral wave patterns (SWPs; Sych & Nakariakov 2014;Su et al 2016;Felipe et al 2019). SWPs apparently propagate radially out at the velocity of around 20 km s −1 , and also propagate upward (Su et al 2016).…”
Section: Introductionmentioning
confidence: 99%